Comparison of dartos flap and dartos flap plus spongioplasty to prevent fistula in tubularized incised plate urethroplasty (Journal of Paediatric Surgeons of Bangladesh, 2018)
Introduction: Hypospadias is one of the most common congenital anomalies and more than 300 operation techniques have been described for primary hypospadias. The complication rate varies with the complexity of the repair and the surgeon’s experience level. To decrease fistula rate, an additional tissue cover after neourethra reconstruction has been described using various tissues. This technique of spongioplasty with dartos flap interposition allows a better quality of the intermediate layer, with the object of preventing fistula.Aims and Objectives: The aim of our study is to evaluate the role of paraurethral spongial tissue plus dartos flap using an additional tissue cover to prevent fistula formation in patients who underwent urethroplasty with the Snodgrass technique. Materials and Methods: It’s a prospective study, performed on 60 patients aged 15 months to 144 months who underwent mid penile and distal hypospadias repair using the Snodgrass technique. The patients were assigned to one of the two groups. In Group I (30 patients), neourethra was covered with dartos flap, and in Group II (30 patients), the neourethra was covered with dartos flap plus spongioplasty. Results: Urethral fistula were encountered in twelve cases (40%) in Group I, and five cases 16.7%) in Group II (p value 0.045).Conclusions: Considering the results of this study, approximation of the corpus spongiosum along with dartos flap as an intermediate layer in urethral coverage as part of Snodgrass technique reduces the rate of fistula formation. This procedure can be applied easily and effectively to prevent the formation of fistula.Journal of Paediatric Surgeons of Bangladesh (2017) Vol. 8 (1): 5-10